Ranga i miejsce planu zagospodarowania przestrzennego w systemie form aktywności samorządu terytorialnego - Jasiński, Witosław J. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
Artykuł porusza jeden z najważniejszych problemów funkcjonowania samorządów. Porządek społeczny i gospodarczy, perspektywy awansu, a także zrównoważony rozwój danego terenu są uzależnione w sposób bezpośredni od prawidłowego uchwalenia i konsekwentnego przestrzegania miejscowego planu zagospodarowania przestrzennego. W artykule podejmuję próbę przedstawienia w sposób skondensowany procedury planowania przestrzennego na poziomie gminy, analizę najważniejszych elementów obowiązującej w tym zakresie ustawy oraz założeń najnowszego projektu aktu prawnego o zagospodarowaniu przestrzennym gmin.

The article considers one of the most important problems in the functioning of territorial self-governments. The social and economic order, perspectives of the promotion of a local territory, as well as a balanced development, are made dependent on the properly created and then the consequently executed plan of the area development. So in this article I try to present briefly the procedures and the process of the planning of the area development on the level of the local community. I analyze the most important dements of the standing legal act and assumptions of the newest project the communes’ area designing act.
Rank and Place of the Plan of the Area Development in the Performance of Territorial Self-Government